Pencegahan Kekerasan Rumah Tangga Melalui Pendidikan Keluarga dalam QS. Al-Tahrim 66: 6 - Izzal Afifir Rahman; Nasrulloh Nasrulloh (Ridwan Institute, 2021)
This study aims to explain family education based on Q.S al-Tahrim, 66: 6 which can be the basic foundation in realizing the welfare of family life so that it is expected to be a solution to acts of domestic violence. In addition, the method used in this research is qualitative by using phenomenological approach in data retrieval. The results explain that family education values are the best solution to prevent domestic violence conflict. On the contrary, the away values of family education can actually create social conflicts in family relationships. Thus, knowledge of quality family education has an important role that can affect family life because family education can create a generation of high-intellectual and good character that benefits both the family and society. An important factor to encourage family education to run well is social responsibility towards the role of each member. Through the Qur'an, the encouragement of family education becomes a motivational spirit in applying family education so that it becomes the key to knowledge that becomes the ideal solution to domestic violence conflict.